Funktioniert die Working-Out-Loud-Methode im universitären (DaF-)Unterricht? - Ágnes (FILOGI, 2020)
Working Out Loud (WOL) is a learning and working method widely used by big companies in more than 50 countries. The members of WOL circles achieve significant progress in their profession while utilizing its techniques. Stories exemplifying the success of this method raise the following question: can we adapt and use it in higher education where new tools for meeting the demands of the labour market are needed? This article attempts to answer the question using data deriving from empirical research.